ANALISIS KELAYAKAN FINANSIAL USAHATANI KELAPASAWIT DI KECAMATAN MUKOK KABUPATEN SANGGAU - Maisaroh, Is Nani; Yurisinthae, Erlinda; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2018)
This research aimed to analyze the financial feasibility level of oil palm farming in Mukok District, Sanggau District. The location of the research was chosen purposely in Semanggis Raya Village, Mukok Sub-district, Sanggau District which is palm oil production center and which is characterized by the high number of production and farmer that are making efforts to palm oil compared with other villages existing in Mukok Sub-district.The number of samples from 40 oil palm farmer. The analysis used is NPV (Net Present Value), IRR (Internal Rate Of Return), B / C Ratio, PP (Payback Period), Sensitivity. The results of the study NPV as much as Rp 82.184.124,62, Net B/C Ratio as much 4,35 and IRR as much 29% and PP for 6 years 4 months. Sensitivity analysis shows is there is an increase of operational cost (fertilizer price) equal to 2,47% and if there is a decrease of benefit equal to 0,51% of oil palm farming in Semanggis Raya village of Mukok distric of Sanggau regency is feasible to cultivate.